IMPLEMENTASI NILAI-NILAI PENGAJARAN DOKTRIN SANCTUARYDI KALANGAN ANGGOTA GEREJA MASEHI ADVENT HARI KETUJUHSEKOTAMADYA PEMATANGSIANTAR - Elfri Darlin Sinaga (Jurnal Theologia Forum STFT Surya Nusantara, 2017)
The doctrine of sanctuary is absolutely necessary to be implemented by every church member of the Seventh-Day Adventist. The implementation of that teaching values of Sanctuary doctrine is veryimportant to all church membersbecause they need more of the required preparation with regards to the time of judgment and preparation for the Second coming of Christ. Some of the preparations required concerning to the work of the mediation of Christ in the Sanctuary, such as: to reject all forms of deviant teaching from the Bible, to conduct heart investigations and settle personal sins through repentance and confession of sin, and pray with a sincere heart to obtain sanctification and assurance of salvation. The last phaseof the priesthood ministration of Christis to conduct the cleansingof sinsof His peoplefromthe book of the recordsin Heavenas describedin the work ofthe high priestinthe annualservicein the earthly Sanctuary. But facts show that many of the church members lack of the required preparation for the time of investigative judgment and preparation for the second coming of Christ.The result of this study indicated that the level implementation of the teaching values of Sanctuary Doctrine among the church members was on the score value 2.5857 (partly implemented or not fully implemented). Based on the result, this research will give some input to church’s pastor in order to improve the spiritual life of his church members, especially amongthe memebers of Seventh-Day Adventist Church in Pematangsiantar municipality